2010
DOI: 10.1108/02640471011033576
|View full text |Cite
|
Sign up to set email alerts
|

College students' misunderstandings about copyright laws for digital library resources

Abstract: PurposeThis paper has two primary purposes: to explore common copyright‐related problems that arise when librarians promote the use of digital library resources; and to investigate college students' misconceptions of copyright laws that arise when the students use these resources.Design/methodology/approachFour librarians in charge of the management of digital library resources were interviewed regarding student‐users' problematic copyright‐infringement behaviors that these librarians often encountered when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…With the convenience of digital copy-and-paste techniques, student cheating with an emphasis on plagiarism has changed and expanded. Baruchson-Arbib and Yaari (2004) investigated the differences between acts of plagiarism from the print era and those from the Internet era, and found that, according to many student respondents, "Information on the Internet belongs to the public domain" (p. 5) (see also Wu, Chou, Ke, & Wang, 2010).…”
Section: Types Of Student Copy-and-paste Practicesmentioning
confidence: 97%
“…With the convenience of digital copy-and-paste techniques, student cheating with an emphasis on plagiarism has changed and expanded. Baruchson-Arbib and Yaari (2004) investigated the differences between acts of plagiarism from the print era and those from the Internet era, and found that, according to many student respondents, "Information on the Internet belongs to the public domain" (p. 5) (see also Wu, Chou, Ke, & Wang, 2010).…”
Section: Types Of Student Copy-and-paste Practicesmentioning
confidence: 97%
“…Fewer efforts are dedicated to determining the levels of knowledge and depths of misunderstanding that students have today. Two research studies carried out in Taiwan (Chou, Chan, & Wu, 2007;Wu, Chou, Ke, & Wang, 2010) underline the confusion and erroneous interpretations, e.g., that all contents available on the Internet are free to use, at no cost; that all educational uses constitute fair use; and that any downloading is permitted for students paying tuition. Also deserving mention here is the study by the Joint Information Systems Committee (2012) focusing specifically on doctorate students, again reflecting the generalized absence of clarity when it comes to copyright related with the publication and diffusion of one's PhD research.…”
Section: Introductionmentioning
confidence: 97%
“…14 Misunderstanding and misinterpretation of copyright laws in addition to THE IMPORTANCE OF IDENTIFYING AND ACCOMMODATING E-RESOURCES USAGE DATA FOR THE PRESENCE OF OUTLIERS | LAMOTHE 33 unfamiliarity with and general apathy toward these same copyright laws further contribute to unlawful downloading of protected material. 15 Many students are unaware that the transmission of downloaded articles violates copyright laws and license agreements and often misunderstand the fair use aspect of copyright as meaning that the acquisition and distribution of licensed content for the purpose of education is allowed. 16 In the minds of these students, distribution is permitted provided it is not for profit.…”
Section: Introductionmentioning
confidence: 99%
“…18 Aggravating the situation are students who firmly believe that by paying tuition they have permission to do whatever they wish with their institutions' e-resources. 19 Some of these same students even use web robots to download as much as possible thereby saving them time and energy. 20 They consider the downloaded item as their personal property.…”
Section: Introductionmentioning
confidence: 99%